A rolling horizon optimization approach for dynamic airspace sectorization. (March 2020) - Wong, C.S.Y.; Suresh, S.; Sundararajan, N.
Abstract: Dynamic airspace sectorization is the concept of dynamically changing the airspaces that the air traffic controllers are managing to handle sudden changes in the air traffic patterns and also the non-availability of certain airspaces due to weather or other considerations. For the dynamically changing sector shapes to be operationally feasible, air traffic controllers need to be familiar with the sector shapes i.e. the new sector shapes need to have a high level of similarity with the previous sector shapes. This paper presents a rolling horizon optimization approach to plan and handle the above problem. Normally in a conventional dynamic airspace sectorization optimization approach, one changes the sector shapes for the next hour interval based on the current sector shapes and the planned next hour traffic pattern. However, in this paper, we propose a rolling horizon optimization approach where the shapes are changed based on a finite horizon of the traffic in future time intervals. Detailed performance evaluation of the proposed method is presented based on Singapore flight information region traffic and historical data. The results clearly show that the proposed approach is better able to provide feasible gradually changing sector shapes that are more suitable for operations when compared to the conventional approach.